The influence of autoclave sterilization on the cyclic fatigue of M-wire rotary endodontic instruments - Stošić, Nenad; Popović, Jelena; Stanković, Antonije; Mitić, Aleksandar; Nikolić, Marija; Todorović, Kosta (Vojnosanitetski pregled, 2024)
Background/Aim. The most important moment in modern endodontics is the inclusion of rotating instruments made of nickel-titanium alloy in daily clinical work, which have supplanted stainless steel instruments due to their superior properties. The aim of this study was to investigate the influence of autoclave sterilization on cyclic fatigue (CF) in two types of rotating instruments produced by M-wire technology with different types of rotation. Methods. This research included two types of M-wire rotary instruments – 48 ProTaper Next® instruments with full rotation and 48 WaveOne® Gold instruments with reciprocating rotation. Each of the two groups of instruments was divided into four additional groups of 12 instruments depending on the number of cycles of sterilization in the autoclave. The instruments were tested in an artificial canal with a 2 and 5 mm radius of curvature. Results. Statistically significantly higher resistance to CF was observed with WaveOne® Gold compared to ProTaper Next® (p < 0.001) instruments, both in the non-sterilized group and after their exposure to the first, third, and fifth cycle of sterilization. The third and fifth cycle of sterilization significantly reduced resistance to CF in the WaveOne® Gold (p < 0.001) group. There was no statistically significant difference in CF resistance between sterilized and non-sterilized instruments of the ProTaper Next® group. Conclusion. Sterilization in an autoclave for instruments based on M-wire technology did not increase resistance to CF.